2019
DOI: 10.1017/s1047951119002269
|View full text |Cite
|
Sign up to set email alerts
|

A beneficial technique for preventing the device protrusion to the aorta during percutaneous patent ductus arteriosus closure: “Balloon-assisted device releasing technique”

Abstract: Background:Although percutaneous closure of patent ductus arteriosus is an established safe procedure, protrusion of the device to descending aorta may occur in various degrees during these procedures, especially in small infants. The aim of our study is to evaluate the benefits of balloon-assisted device releasing technique in the era of preventing device protrusion and conditions related to protrusion.Methods:One hundred and fifty-five infants, who underwent patent ductus arteriosus closure with Amplatzer du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Serious transcatheter closure-related complications, such as embolization and arterial injury [10], cannot be ignored. Embolism is commonly caused by insertion of an undersized device, incorrect positioning, and erroneous operation [11][12][13], whereas arterial injuries are caused by iatrogenic coarctation or aortic dissection due to smaller aortic dimension, poor arterial elasticity, and aortic wall abrasion secondary to the disk at the aortic side, among others [14,15]. Therefore, a correct-sized occluder should be selected when performing transcatheter closure and the condition at post-implantation morphologically examined [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious transcatheter closure-related complications, such as embolization and arterial injury [10], cannot be ignored. Embolism is commonly caused by insertion of an undersized device, incorrect positioning, and erroneous operation [11][12][13], whereas arterial injuries are caused by iatrogenic coarctation or aortic dissection due to smaller aortic dimension, poor arterial elasticity, and aortic wall abrasion secondary to the disk at the aortic side, among others [14,15]. Therefore, a correct-sized occluder should be selected when performing transcatheter closure and the condition at post-implantation morphologically examined [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a correct-sized occluder should be selected when performing transcatheter closure and the condition at post-implantation morphologically examined [8]. The use of a balloon-assisted release method intraoperatively has been recommended to prevent the occluder from protruding to the aorta during the PDA catheter occlusion [14]. Ireneusz et al [16] reported an interesting case of a 10-month-old girl with severely narrowed aorta after the PDA transcatheter occlusion, requiring an emergency surgery to remove the occluder to prevent severe cardiac failure.…”
Section: Discussionmentioning
confidence: 99%